An Evaluation of Graduate Students' Perceptions in ICT Utilization - Suleiman, Yusuf; Ibrahim-Raji , Tinuke Bilikis (Universitas Pendidikan Ganesha, 2024)
Currently there is a gap in perception, use and access to ICT among postgraduate students at private universities. This is caused by factors related to aspects of the individual, such as gender and educational attainment. Therefore, this study was conducted to analyze postgraduate students perceived the use of and influence of ICT in their research efforts. The study used a descriptive survey design. The researcher chose 100 postgraduate students at random from each of the faculties at university to complete the survey questionnaire. To find out if the measurement tools were reliable and consistent, a reliability test was done. The results show that ICT utilization among postgraduate students is essential for their research work. However, many students are not perfect in the usage of ICT devices despite their availability in the school and their environment. Therefore, students should be encouraged to use ICT devices in their research activities. The usage of ICT would help the students to be more effective and efficient in their research activities.